THE INFLUENCE OF THE ACTUALIZATION OF PACASILA VALUES ON THE STRENGTHENING OF STUDENT CHARACTER - Odang Hermanto; Fiqni Nur Ramadhina; Jamilah (Journal Civics And Social Studies, 2024)
This study aims to determine how much influence the actualization of Pancasila values ​​of students. The method that researchers used in this research is descriptive analysis method with a quantitative approach. Data collection techniques used are observation, questionnaires, and documentation. Sources of data obtained from class X students of SMAN 1 Garut. This study shows that, there is an influence of the actualization of Pancasila values ​​in strengthening the character of class X students of SMAN 1 Garut. By actualizing the values ​​of Pancasila and applying its values ​​in everyday life, it will affect the character of students. Students apply Pancasila values ​​that have been actualized, so their character will also have an effect. This is evident from the research results of 43.4% that the actualization of Pancasila values ​​influences the character of students and the other 56.6% is influenced by attitudes of nationalism and patriotism. The implementation of the actualization of Pancasila values ​​and the character of students is not only the responsibility of Civics and religion teachers but is the responsibility of all teachers and elements of society, therefore in its application all teachers and elements of society can pay attention.